2006
DOI: 10.1091/mbc.e06-07-0606
|View full text |Cite
|
Sign up to set email alerts
|

Novel Function of Clathrin Light Chain in Promoting Endocytic Vesicle Formation

Abstract: Clathrin-mediated endocytosis is a major pathway for uptake of lipid and protein cargo at the plasma membrane. The lattices of clathrin-coated pits and vesicles are comprised of triskelions, each consisting of three oligomerized heavy chains (HC) bound by a light chain (LC). In addition to binding HC, LC interacts with members of the Hip1/R family of endocytic proteins, including the budding yeast homologue, Sla2p. Here, using in vivo analysis in yeast, we provide novel insight into the role of this interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 33 publications
5
50
0
Order By: Relevance
“…The protein contains the ANTH, coiled-coil, and THATCH domains present in all HIP1 proteins. The coiled-coil domain in Sla2p and HIP1 enables binding to clathrin-light chain, although the exact mode of interaction differs from yeast to mammals, suggesting differences in the regulation of intracellular transport among different species (LegendreGuillemin et al, 2005;Newpher et al, 2006;Ybe et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein contains the ANTH, coiled-coil, and THATCH domains present in all HIP1 proteins. The coiled-coil domain in Sla2p and HIP1 enables binding to clathrin-light chain, although the exact mode of interaction differs from yeast to mammals, suggesting differences in the regulation of intracellular transport among different species (LegendreGuillemin et al, 2005;Newpher et al, 2006;Ybe et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…and KDEQIKN in yeast (Chen and Brodsky, 2005;LegendreGuillemin et al, 2005;Newpher et al, 2006;Ybe et al, 2007). A similar sequence is present in HIPR-1 and corresponds to 458 KDEEITA.…”
Section: Discussionmentioning
confidence: 97%
“…Each triskelion is drawn as a "worm" extending from the hook-like representation of the terminal domain on the inside of the shell to the vertex of the triskelion at the outside. by recruitment of HIP1R by the amino-terminal segment of both species (Chen and Brodsky 2005;Newpher et al 2006). …”
Section: Clathrinmentioning
confidence: 99%
“…Shared sequences of 22 and 10 residues, respectively, mediate binding to the actin-organizing huntingtin-interacting proteins (mammalian Hip1 and Hip1R, yeast Sla2p) (10)(11)(12) or the leucine-rich repeat kinase 2 (LRRK2) (13). Mammalian cell culture experiments and genetic studies in yeast and flies have shown that, through these interactions, CLCs participate in several pathways that could significantly affect clathrin function in vertebrates.…”
mentioning
confidence: 99%